PENGGUNAAN SAPAAN KEKERABATAN BAHASA MAKEAN DIALEK SAMSUMA DI DESA SAMSUMA KECAMATAN MALIFUT - Habsi, Rini (Universitas Sam Ratulangi, 2018)
This article discusses about greeting words in Makean language in Malifut district North Halmahera regency. There are two matters in this article; first, what are the kindship greetings used in Makean language Samsuma dialect. And the second, how to use the greeting words to the family relationship in Makean language in Malifut district. The research is emphasized in sociolinguistic. The research uses descriptive method. This research was held in Malifut district, North Halmahera regency of North Malucas Central. The technique of gathering data is listening technique and conversation technique. The family greeting words in the in the nuclear family in Samsuma dialect Makean language namely baba (faather), mama (mother), jojo (sister of mother), theno (younger sister or brother), tamno (elder brother or male cousin). The use of greeting words in the Samsuma dialect Makean language different of the Javanese language and so on because its use is not used for people who are spoken but to make or answer questions.Keywords: Greeting words, Makean Language, Samsuma Dialect, familyÂ